A new history of classical rhetoric - Kennedy, George Alexander 1928-; Kennedy, George Alexander 1928-; Kennedy, George Alexander 1928-; Kennedy, George Alexander 1928-; IG Publishing (Princeton, N.J. Princeton University Press, 1994)
George Kennedy's three volumes on classical rhetoric have long been regarded as authoritative treatments of the subject. This new volume, an extensive revision and abridgment of The Art of Persuasion in Greece, The Art of Rhetoric in the Roman World, and Greek Rhetoric under Christian Emperors, provides a comprehensive history of classical rhetoric, one that is sure to become a standard for its time.
Ch. 1. Introduction: The Nature of Rhetoric -- Ch. 2. Persuasion in Greek Literature before 400 B.C. -- Ch. 3. Greek Rhetorical Theory from Corax to Aristotle. Plato's Gorgias. Plato's Phaedrus. Isocrates. The Rhetoric for Alexander. Aristotle -- Ch. 4. The Attic Orators. Lysias. Demosthenes -- Ch. 5. Hellenistic Rhetoric. Theophrastus. Later Peripatetics. Demetrius, On Style. The Stoics. The Academics. The Epicureans. Asianism. Hermagoras and Stasis Theory -- Ch. 6. Early Roman Rhetoric. Cato the Elder. Roman Orators of the Late Second and Early First Centuries B.C. Latin Rhetoricians. Cicero's On Invention. The Rhetoric for Herennius -- Ch. 7. Cicero. Cicero's Orations in the Years from 81 to 56 B.C. On the Orator. For Milo and Cicero's Later Speeches. Brutus and Orator -- Ch. 8. Rhetoric in Augustan Rome. Greek Rhetoricians of the Second Half of the First Century B.C. Dionysius of Halicarnassus. Declamation and Seneca the Elder -- Ch. 9. Latin Rhetoric in the Silver Age.
"An extensive revision and abridgement of The art of persuasion in Greece, The art of rhetoric in the Roman world, and Greek rhetoric under Christian emperors, with additional discussion of Late Latin rhetoric."
Electronic reproduction.
Keywords: Rhetoric, Ancient; Speeches, addresses, etc., Greek -- History and criticism; Speeches, addresses, etc., Latin -- History and criticism; Persuasion (Rhetoric); Oratory, Ancient; Electronic books